Thymic dysplasia with normal immunoglobulins (the Nezelof syndrome) (a case report) - Berkel, A. İzzet and Çağlar, Melda and Tınatepe, Keriman and Ersoy, Fügen (The Turkish Journal of Pediatrics, 1976)
Thymic dysplasia with normal immunoglobulins is a form of primary immunodeficiency occurring in infancy. Its clinical picture is indistinguishable from severe combined immunodeficiency with decreased or absent immunoglobulins. A similar picture to that seen in Nezelof syndrome may also be observed in patients with severe marasmus indicating that these two entities have to be differentiated occasionally. This report concerns an 11-month old boy with severe malnutrition, normal immunoglobulins, decreased serum complement (C3) level and depressed cellular immunity. Surprisingly, post mortem examination revealed a small dysplastic thymus and small lymph nodes with marked depletion of lymphocytes in thymic dependent areas while plasmocytes were present. It is suggested that in marasmic infants with severely depressed cellular immunity and normal immunoglobulins the possibility of Nezelof syndrome should be considered with further appropriate immunologic investigations.